Sustentabilidade na Gestão Pós-Uso de Produtos Tecnológicos: Um Estudo na Universidade Federal do Espírito Santo - UFES - Lupe, Gedson Zucolotto (2024)
The generation and accumulation of electronic waste represent a serious problem for society as a whole. When these materials are not managed properly, they can cause significant negative impacts on the environment, even resulting in biodiversity loss. In this context, sustainable development plays a fundamental role in all sectors, including the public sector, which should conduct its activities in accordance with best environmental practices. Within the Federal University of Espírito Santo, issues related to the management of post-use electronic materials were identified. Many equipment items, such as computers, monitors, and printers, are stored for long periods without receiving environmentally, socially, and economically appropriate disposal. Therefore, the main objective was to analyze potentials and opportunities for implementing sustainable practices in the management of stored computer electronic materials at the Property Division Warehouse of the Federal University of Espírito Santo. The theoretical framework was based on aspects of sustainable development applied to the public sector, such as the A3P Agenda, the 2030 Environmental Agenda of the United Nations, Decree 9.373/2018, and Federal Law No. 14.479/2022, as well as on asset management in public administration, especially related to post-use of assets. The research adopted a mixed approach and was conducted at the Property Division of the Federal University of Espírito Santo. Four sources of research were explored. The first source consisted of employees and staff of the Property Division; the second consisted of employees responsible for requesting the collection/transfer of unusable goods to the Property Division Warehouse; the third source analyzed documents related to the registration of entry and exit of these goods from the warehouse, as well as their acquisition by the University; finally, the fourth source was based on bibliographic research on the studied theme. Data collection instruments included questionnaires and analysis of asset reports generated within the University. The results showed challenges in electronic waste management at Federal University of Espírito Santo in 2022 and 2023. There was a large amount of electronic equipment destined for the Property Division Warehouse, with limited capacity and inadequate space, without proper separation of materials, nor trained personnel for technical evaluation of these assets, as well as institutional incentive for repair and reuse of assets. This scenario highlights the need for policies and programs for more efficient and sustainable management of computer electronic waste at the Federal University of Espírito Santo. Based on the results, as a technological product, a proposal for a normative instruction was elaborated establishing rules for a sustainable policy of reuse, repair, and disposal of permanent movable assets at the Federal University of Espírito Santo.